A real-life analysis of patients with rheumatologic diseases on biological treatments: Data from TURKBIO registry - İNANÇ, GÜZİDE NEVSUN; DİRESKENELİ, RAFİ HANER (My University, 2022)
Objective: TURKBIO registry, established in 2011, is the first nationwide biological database in Turkey. This study aimed to provide an overview of TURKBIO data collected by June 2018. Methods: The registry included adult patients with rheumatoid arthritis (RA), ankylosing spondylitis (AS), nonradiographic axial spondyloarthritis (nr-AxSpA), and psoriatic arthritis (PsA). Demographic and clinical features, disease activity markers, and other follow-up parameters, current and previous treatments, and adverse events were registered electronically at each visit using open-source software. The registration of patient-reported outcome measures was carried out electronically by the patients using touch screens. Results: TURKBIO registry included a total of 41,145 treatment series with biologicals. There were 2,588 patients with axSpA (2,459 AS and 129 nr-axSpA), 2,036 with RA, and 428 with PsA. The total number of patients, including those with other diagnoses, was 5,718. In the follow-up period, the number of patients and also visits steadily increased by years. The yearly mean number of visits per patient was found to be 2.3. Significant improvements in disease activity and health assessment parameters were observed following the biological treatments. Biologics were often given in combination with a conventional synthetic disease-modifying antirheumatic drug in patients with RA. Infections were the most commonly seen adverse events, followed by allergic reactions. Tuberculosis was observed in 12 patients, malignancy in 18, and treatment-related mortality in 31. Conclusion: TURKBIO provided a valuable real-life experience with the use of biologics in rheumatic diseases in Turkey
Keywords: ROMATOLOJİ; Klinik Tıp; Klinik Tıp (MED); RHEUMATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Biologic registry; rheumatic disease; Turkey; AXIAL SPONDYLOARTHRITIS; ARTHRITIS PATIENTS; TIGHT CONTROL; PREVALENCE; IZMIR; EFFICACY; Biologic registry; rheumatic disease; Turkey